Growth Performance of Heifers Under Different Systems of Grazing on Dichonthium- Aristido Pasture in Semi-Arid Regions of Rajasthan - Verma, C M; Ahuja, L D (Annals of Arid Zone, 2016)
In order to evaluate the livestock production on rangelands under Dichanthium-Aristida cover with a mean annual rainfall of 553 mm, different systems of rotational grazing were studied during the period from 1970-76. The studies revealed that the growth rate of yearling heifers was not significantly affected by the different treatments of grazing management viz. continuous controlled grazing and grazing during different rotational periods. The growth rate of these heifers ranged between 48.4 to 88.0 kg/animal in a year. However, the growth rate of t,he yearling heifers was significantly affected by the seasons (periods) irrespective of the years and the treatments of grazing. The highest growth rate have been observed during August-September followed in the month of October-November, the least being during the months’ of April and May. The growth rate during the month of August-September was quite high and average to 13.0 kg per animal per month and it compares favourably to the animals maintained on the farms under fairly high level of nutrition.